A Functionally Graded Cathode Architecture for Extending the Cycle‐Life of Potassium‐Oxygen Batteries. Issue 8 (12th August 2019) - Gilmore, Paul; Sundaresan, Vishnu Baba
Abstract: Invited for this month's cover picture is the group of Prof. Vishnu Baba Sundaresan. The cover picture shows a functionally‐graded cathode for potassium‐oxygen batteries, regulating K + ‐ion and oxygen transport at the trilayer electrolyte‐cathode‐air interface. Read the full text of the article at10.1002/batt.201900025 Abstract : "The crossover of molecular oxygen from cathode to anode limits the cycle‐life of K−O2 batteries. The cover graphic has been designed to illustrate the K + ‐ion and oxygen transport at the trilayer electrolyte‐cathode‐air interface, regulated by a newly developed functionally‐graded cathode (FGC) architecture. A K−O2 battery fabricated using this FCG lasts >125 cycles with minimal loss in coulombic efficiency. The combination of performance and cost of about $44 kWh −1 renders this architecture as a promising candidate for electrochemical energy storage devices for stationary applications." Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding article on10.1002/batt.201900025